2006
DOI: 10.1097/01.mpg.0000232572.56397.d6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prenatal Lipopolysaccharide Exposure on Epithelial Development and Function in Newborn Rat Intestine

Abstract: Maternal exposure to LPS during pregnancy alters intestinal growth and regulation of iNOS in the newborn rat intestine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Recently prenatal inflammation, in the form of chorioamnionitis, has been shown to predispose infants to the development of NEC. We have shown that rat pups exposed to prenatal inflammation have decreased mucosal growth and intestinal barrier function as well as altered NO regulation (Giannone et al, 2006). These may all be contributory mechanisms to the development of NEC in infants born to mothers with chorioamnionitis and add further insight into possible inflammatory etiologies of this disease.…”
Section: Speculative Mechanisms: the Role Of Inflammation In Nec And Chdmentioning
confidence: 97%
“…Recently prenatal inflammation, in the form of chorioamnionitis, has been shown to predispose infants to the development of NEC. We have shown that rat pups exposed to prenatal inflammation have decreased mucosal growth and intestinal barrier function as well as altered NO regulation (Giannone et al, 2006). These may all be contributory mechanisms to the development of NEC in infants born to mothers with chorioamnionitis and add further insight into possible inflammatory etiologies of this disease.…”
Section: Speculative Mechanisms: the Role Of Inflammation In Nec And Chdmentioning
confidence: 97%
“…For example, maternal smoking during pregnancy may cause reno-vascular changes (28) and elevated blood pressure. (29)Maternal exposure to endotoxin can result in fetal brain damage in the sheep (30) or altered intestinal growth and barrier function in the rat (31).…”
Section: Research Is Emerging On Developmental Disruption By Environmmentioning
confidence: 99%
“…The association between reduced nephron number and the development of hypertension has been well documented by Giannone PJ et al [7]. It can be explained that prenatal exposure to zymosan might have affected the renal development and caused decreased glomerular number.…”
Section: Discussionmentioning
confidence: 85%
“…Antenatal insults, including infections and inflammation, have been implicated in alterations of development, leading to increased incidences and/or severities of diseases of later onset [7]. Maternal protein or calorie restriction, as well as exposure to glucocorticoids during pregnancy, programmed hypertension and a reduced glomerular (nephron) number in offspring [8][9][10][11][12] Zymosan, a component of yeast cell walls comprised mainly of β-glucan and mannan, is a specific ligand for TLR2/6 and is capable of inducing inflammation that mimics a non-bacterial inflammatory response [13].…”
Section: Introductionmentioning
confidence: 99%